Explaining and Examining Mullā Ṣadrā's Response to the Doubt of Incompatibility of Concomitance of Satisfaction to Divine Decree with Satisfaction to Evil - Ruhollah Zeinali (آموزه‌‌های فلسفه اسلامي, 2021)
The doubt of incompatibility of concomitance of satisfaction to divine decree with satisfaction to evil is one of the most important challenges facing the belief in the generality of divine will and decree and ordinance (predestination). Knowing real evil negatively and the separation (distinction) of decree and predestined thing, the separation of essential and incidental in the mode of being and the separation in the mode of the existential and essential aspects and the emphasis on the dominance of the existence-oriented attitude in virtual evil are the answers that can be obtained from Mullā Ṣadrā's works. Examination of these answers shows that negative knowing is faced with the problem of the circle of its argument. Separation of decree and predestined thing is also not a solution due to the inability to prove the real difference. In the essential and incidental distinction (separation), doubt on the arbitrary existence of evil can still be raised. But in Mullā Ṣadrā's final answer that principality in the principality of existence means being outside and multiplicity in the unity of existence also means the manifestations of existence, the doubt is fundamentally removed.